Caps on political contributions, monetary penalties and politician preferences - Ivan Pastine; Tuvana Pastine (University College Dublin, UCD School of Economics, 2009)
With politician preferences over policy outcomes, the effect of a contribution cap with monetary penalties for exceeding the cap is starkly different from the case with an indifferent politician. In contrast to Kaplan and Wettstein (AER, 2006) and Gale and Che (AER, 2006), a cap is never neutral on the expected cost of contributions nor on the policy outcome. Furthermore more restrictive caps can lead to increased aggregate contributions. When the penalty for exceeding the cap is small enough that it is impossible to suppress all contributions, the influence of money on policy is minimized with a binding but non-zero cap and maximized with no cap.
hdl:10197/2609
Keywords: D72; C72; 330; All-pay auction; Campaign finance reform; Soft money; Explicit ceiling; BCRA